ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE TERHADAP PERTENGKARAN RUMAH TANGGA DALAM FILM “PERFECT STRANGERS” - Firmansyah, Herwin; S.S., M.A., Tsuroyya (Universitas Negeri Surabaya, 2024)
Film is a medium that is often used to represent social reality. The reality of marriages and household disputesis often shown in scenes with the aim of conveying a certain message, as was done in the film